How two leading partners learn to tango: The case of IoT-based business model co-innovation between a retailer and an electronics supplier - Michael Sturm; Jörg Weking; Markus Böhm; Maximilian Schreieck; Helmut Krcmar (Electronic Markets, 2023)
Due to eroding business models, companies are seeking new growth opportunities. Business model innovation (BMI) can enable sustainable competitive advantage and future growth. Yet many companies are struggling to innovate their business models. Recent research reveals that collaboration concerning stakeholder integration and open business model innovation can foster BMI, but research has addressed both topics in isolation. By combining these topics, we establish business model co-innovation (BMCI) as a new perspective. Based on a longitudinal case study of an incumbent retailer and an incumbent electronics supplier, we investigate how both parties contribute to innovating the supplier's business model. We document a BMCI process model highlighting the direct and indirect business model changes of the retailer and the supplier and we identify BMCI characteristics. We contribute to research with a new perspective on how partners co-innovate a business model.
Keywords: O3; 620; Business model innovation; Internet of Things; Innovation